Potential of Diffusion-Weighted Imaging in the Characterization of Malignant, Benign, and Healthy Breast Tissues and Molecular Subtypes of Breast Cancer - Sharma, Uma; Sah, Rani G.; Agarwal, Khushbu; Parshad, Rajinder; Seenu, Vurthaluru; Mathur, Sandeep R.; Hari, Smriti; Jagannathan, Naranamangalam R. (Frontiers in Oncology, 2016)
The role of apparent diffusion coefficient (ADC) in the diagnosis of breast cancer and its association with molecular biomarkers was investigated in 259 patients with breast cancer, 67 with benign pathology and 54 healthy volunteers using diffusion-weighted imaging (DWI) at 1.5 T. In 59 breast cancer patients, dynamic contrast enhanced MRI (DCEMRI) was also acquired. Mean ADC of malignant lesions was significantly lower (1.02 ± 0.17 x 10-3 mm2/s) compared to benign (1.57 ± 0.26 x 10-3 mm2/s) and healthy (1.78 ± 0.13 x 10-3 mm2/s) breast tissues. A cut-off ADC value of 1.23 x 10-3 mm2/s (sensitivity 92.5%; specificity 91.1%; AUC 0.96) to differentiate malignant from benign diseases was arrived by ROC analysis. In 10/59 breast cancer patients, indeterminate DCE curve was seen while their ADC value showed as positive for malignancy implying the potential of the addition of DWI in increasing the specificity of DCEMRI data. Further, the association of ADC with the tumor volume, stage, hormonal receptors [estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor (HER2)] and menopausal status was investigated. A significant difference was seen in tumor volume between breast cancer patients of stages IIA and IIIA; IIB and IIIA; and IIB and III (B + C) (p<0.05). A statistically significant lower ADC and a lower tumor volume was seen in patients with early (n=52) compared to those with locally advanced breast cancer (n=207). No association was found in ADC and tumor volume with the menopausal status. Breast cancers with ER-, PR- and triple negative (TN) status showed a significantly larger tumor volume compared to ER+, PR+ and non-triple negative (nTN) cancers, respectively. Also, TN cancers showed a significantly higher ADC compared to ER+, PR+ and nTN cancers. Patients with ER- and TN cancers were of younger age compared to those with ER+ and nTN cancers. The present study demonstrated that ADC may increase the diagnostic specificity of DCEMRI and aid in treatment management in a clinical setting. Additionally, it provides an insight into characterization of molecular types of breast cancer and may serve as an indicator of metabolic reprogramming underlying tumor proliferation.